Transcriptome responses to benzo[a]pyrene in liver slices of sub-arctic fish species - Brun, Nadja R.; Yadetie, Fekadu; Liestøl, Hanna Todal; Karlsen, Odd André; Goksøyr, Anders (Frontiers in Marine Science, 2024)
Due to the expanding oil-related activities, the arctic and sub-arctic marine environments are increasingly vulnerable to oil-related pollution such as accidental oil spills. These cold-water ecosystems harbor many fish species that are both ecologically and economically important such as the pelagic polar cod (Boreogadus saida), capelin (Mallotus villosus), and benthic long rough dab (Hippoglossoides platessoides). The latter two are much less studied and it is crucial to characterize their responses to oil-related contaminants and develop molecular biomarkers and genomic resources for future monitoring. In this study, liver slice preparation and culture methods were used to characterize the transcriptome responses (using RNA-seq) in capelin and long rough dab to exposures of the polycyclic aromatic hydrocarbon (PAH) compound benzo[a]pyrene (BaP). The liver slice culture and exposure experiments were performed onboard a research vessel in the Barents Sea. Strong up-regulation of genes involved in biotransformation, particularly the aryl hydrocarbon receptor signaling pathway was observed in both species. A comparison of the number of differentially expressed genes (DEGs) with previously published polar cod exposures indicates that the latter responded more strongly (higher number of genes), suggesting higher uptake and bioconcentration of BaP in the fatty liver tissue, although other factors such as differences in clearance rate could potentially affect the responses. This study provides new genomic resources and gene expression biomarkers in capelin and long rough dab, enhancing our understanding of their response mechanism to oil-related contaminants.